Human Perception Of Hand Pain For Activities Common In Daily Life - Kamat, Seri Rahayu; Yoxall, Alaster; Carre, Matt; Rowson , Jenifer (2010)
The hand is one of the essential parts of the body for carrying out Activities of Daily Living (ADLs). Individuals use their hands and fingers in everyday activities either in the workplace or at home. Hand-intensive tasks require diverse and sometimes extreme levels of exertion, depending on the action, movement or manipulation involved. Good design product especially using hand and finger should consider factors such as simplicity ease to learn, efficiency and pleasure of use and should be suitable for general application for all user categories including those with disabilities. Hence, improved understanding of hand pain is important for the study of ADLs and particular attention should be drawn to the type, cause, frequency and degree of pain. Our primary objective was to determine the level and frequency of pain in the hands and fingers during common ADLs and the associated hand actions. The actions investigated were gripping, pinching, twisting, manipulating of digits and lifting. A survey totaling 626 participants was collected using an online survey, with respondents ranging between 22 to 58 years old. 616 subjects fully completed the survey with a response rate of 98.9% with 209 (34%) male and 407 (66%) female. The result shows that gripping produced the highest frequency of pain, but twisting produced the highest degree of pain, followed by pinching. Gripping and lifting actions showed the same degree of average pain rating. Serious pain feeling is ache recording higher percentage (28% - 35%), while tender, sharp, cramp, tingling are within the same range for every action. These results and proposes further work is to improve the design, environment and method to manipulate object.